Gender diversity in job changing researched on the job market of immigrants in dalat city, lam dong province, vietnam - VU, DR. THUY DUNG THI (The journal of contemporary issues in business and government, 2021)
Dalat has recently marked a big change in its economics field, and it is said that such a significant breakthrough cannot be completely fulfilled if there is an ignorance of the role of female immigrants in Dalat. This paper mainly focuses on job changing of female immigrants in Dalat job market together with some other related factors resulting in such an issue. The diversity of genders can be considered not only in the presence in different working fields, working areas, working positions but also in various working movements of immigrants. The two surprising findings of this research can prove that 1/ there is a movement of male workers towards non- agriculturally- related jobs in some regions, whereas there is a domination of female immigrants in the agricultural sector in Dalat city; 2/ Many research papers have already found the important role of social capital regarding job changing, yet in this research paper a blurred vision of this culprit has been found compared with such other factors as motivation, purpose, education The figure of this paper has been extracted from the doctoral thesis of the researcher.